A composite solid-state electrolyte based on solvent intermolecular dipole-dipole interaction, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611245380.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-30
AI Technical Summary
然而,这些策略通常将性能提升归因于Li+与弱溶剂化溶剂的单一作用(如降低脱溶剂化能垒、促进阴离子配位),而忽视了溶剂之间(如氢键、偶极-偶极作用)对溶剂化结构与离子输运的潜在影响
(1) 提出全新调控维度:本发明首次提出利用溶剂间偶极-偶极相互作用作为调控CSE性能的新维度,打破了传统研究中仅关注溶剂-Li+、溶剂-聚合物、溶剂-填料相互作用的单一认知框架。通过引入弱溶剂化溶剂与残留强极性溶剂之间的Hδ⁺-Oδ⁻偶极-偶极作用,从源头系统性削弱了与强极性溶剂关联的多重强相互作用,实现了对溶剂化学与界面化学的协同调控,从根本上解决了离子电导率与界面稳定性之间的两难困境。
Smart Images

Figure CN123018095A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid electrolyte and lithium metal battery technology, specifically relating to a composite solid electrolyte that synergistically regulates ion transport and interface stability through inter-solvent dipole-dipole interactions, its preparation method, and its application in lithium metal batteries. Background Technology
[0002] With fossil fuels becoming increasingly depleted, developing energy storage technologies that combine high energy density, safety, and economy has become a core requirement for sustainable energy transition. Currently commercially available liquid lithium-ion batteries are limited by energy density bottlenecks and flammability concerns, making it difficult to meet the performance requirements of next-generation batteries. Solid-state lithium metal batteries are considered a promising alternative due to their intrinsic safety and high energy density. Among them, composite solid electrolytes (CSEs), using polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP) as the matrix and LLZTO as the filler, combine the advantages of polymers and inorganic electrolytes and are considered one of the most commercially promising candidates. In recent years, researchers have effectively solved problems such as insufficient lithium salt dissociation, poor filler-polymer compatibility, phase separation, and the high crystallinity of PVDF-HFP. However, CSEs still face bottlenecks in practical applications due to insufficient ionic conductivity and poor interfacial stability, severely restricting their large-scale deployment. The root cause of this predicament lies in the long-neglected issue of residual solvents. In the preparation process, highly polar solvents (such as N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), and dimethyl sulfoxide (DMSO)) are widely used to dissolve the polymer and lithium salt. Because the solvent reacts with Li... + There are strong ion-dipole and dipole-dipole interactions between the polymer and filler, and a large amount of solvent remains in CSE, reacting with Li. + They combine to form [Li (solvent)] x ] + Solvated structure.
[0003] With [Li(DMF)] x ] + For example, Li + DMF dynamically couples and decouples from PVDF-HFP through ion-dipole and dipole-dipole interactions, respectively, which to some extent promotes Li + Transmission. However, the strong dipole-dipole interaction between DMF and PVDF-HFP limits the [Li(DMF)] transmission. x ] + Migration along the polymer chain. Simultaneously, DMF and Li... + The high binding energy of Li leads to a solvent-dominated solvation structure, enabling Li to... + The desolvation energy barrier increases, and at the interface [Li(DMF)]... x ] +Li between the filler + The exchange rate decreases, which in turn leads to uneven Li... + Flux and lithium dendrite nucleation. Furthermore, highly polar solvents such as DMF possess high highest occupied molecular orbital (HOMO) energy levels, preferentially decomposing at the cathode interface, leading to high-voltage polarization and cathode structural degradation; their high reactivity with lithium metal triggers continuous side reactions, forming a solid electrolyte interphase (SEI) film rich in organic components, generating a huge interfacial resistance, severely hindering Li-1 lithium production. + Cross-interface transmission.
[0004] It is worth noting that the residual solvent affects Li + Conduction has a dual effect: simply reducing DMF lowers ionic conductivity, while retaining excessive amounts impairs interfacial stability. Therefore, precisely controlling the residual solvent effect without sacrificing ionic conductivity has become a key challenge for achieving stable CSE operation.
[0005] Only in recent years have some studies begun to focus on the effects of residual DMF on interfacial stability and Li. + The adverse effects of transport were investigated, and attempts were made to improve the situation through strategies such as introducing adsorbent fillers (Angew. Chem. 2021, 133, 24873-24880), interfacial functional layers (Small2024, 2406193), additives (Adv. Funct. Mater. 2025, e14960), and controlling the solvent / lithium salt composition and polymer configuration (J. Am. Chem. Soc. 2023, 145, 25632-25642). However, these strategies did not fundamentally reconstruct the unstable solvation structure in the composite electrolyte. References (J. Am. Chem. Soc. 2024, 146, 11371-11381) report the introduction of trifluoroacetamide to partially replace DMF, and Chinese patent application CN116454370A discloses a method of introducing trifluoroacetamide to partially replace DMF with Li. + Schemes that modulate the solvation structure using ligands with weaker coordination ability than DMF (such as N-methyltrifluoroacetamide) by weakening Li + Solvent forces are used to enhance ion conductivity. However, these strategies typically attribute the performance improvement to Li. + The study focuses on the singular effects of weak solvation solvents (such as lowering the desolvation energy barrier and promoting anion coordination), neglecting the potential influence of solvent interactions (such as hydrogen bonding and dipole-dipole interactions) on solvation structure and ion transport. Even with effective modulation of the solvation structure, the strong interaction between the solvent and the polymer still hinders Li + Transport only achieved limited performance improvements and failed to fundamentally resolve the trade-off between ionic conductivity and interfacial stability, leading to the degradation of the Li in the electrolyte. +Electrical conductivity (<10) -3 S cm -1 Key electrochemical properties, such as electrochemical performance, still cannot meet the needs of practical applications.
[0006] In summary, existing strategies cannot fundamentally achieve both precise control of the residual solvent effect and Li + Breakthrough in transmission restrictions. Summary of the Invention
[0007] To address the shortcomings of existing technologies, this invention provides a composite solid electrolyte based on solvent-dipole-dipole interactions, its preparation method, and its applications. It aims to solve the technical challenge of the trade-off between ionic conductivity and interfacial stability in existing composite solid electrolytes caused by residual highly polar solvents (such as DMF). This invention provides a multi-dimensional synergistic control of the residual solvent effect, enabling the simultaneous achievement of high ionic conductivity and high Li- content. + Composite solid electrolytes with high migration number and excellent interfacial stability and their preparation methods.
[0008] The objective of this invention can be achieved through the following technical solution: a composite solid electrolyte, characterized in that the electrolyte comprises: a polymer matrix, a lithium salt, an inorganic filler, and a solvent system; the solvent system comprises a strongly polar solvent A and a weakly solvating solvent B; the strongly polar solvent A has a reaction with Li + Strong coordination / dipole-dipole interactions between the polymer matrix and inorganic fillers; the weakly solvating solvent B, which has a strong affinity for Li + The coordination ability, polymer matrix, and inorganic filler coordination strength of the weakly solvating solvent B are weaker than those of solvent A; an intermolecular dipole-dipole interaction exists between the weakly solvating solvent B and the strongly polar solvent A, and this dipole-dipole interaction can induce a redistribution of the electron cloud density of the strongly polar solvent A, thereby weakening the interaction between the strongly polar solvent A and Li. + The interaction strength between the polymer matrix and the inorganic ceramic filler.
[0009] Preferably, the highly polar solvent A is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, dimethyl sulfoxide, or carbonate solvents, and more preferably N,N-dimethylformamide (DMF).
[0010] Preferably, the weak solvating solvent B is selected from one or more of ether solvents, fluorinated amide solvents, fluorinated pyridine solvents, phosphate ester solvents, or fluorinated sulfonamide solvents.
[0011] More preferably, the ether solvent is selected from one or more of cyclopentylmethyl ether, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, methyl tert-butyl ether, or ethyl tert-butyl ether, preferably cyclopentylmethyl ether (CPME); the fluorinated amide solvent is selected from one or more of trifluoroacetamide, N-methyltrifluoroacetamide, N,N-dimethyltrifluoroacetamide, or N-methoxy-N-methyltrifluoroethanesulfonamide; and the fluorinated pyridine solvent is selected from one or more of fluoropyridine.
[0012] Preferably, the molar ratio of the weak solvating solvent B to the strong polar solvent A is 1:4 to 4:1, more preferably 1:2 to 2:1.
[0013] Preferably, the polymer matrix is selected from one or more of polyethylene, polypropylene, polyvinyl chloride, polyvinylidene fluoride, polyvinylidene fluoride hexafluoropropylene, polyethylene oxide, polyacrylonitrile, polymethyl methacrylate or polyvinylidene chloride, and more preferably polyvinylidene fluoride hexafluoropropylene (PVDF-HFP).
[0014] Preferably, the dipole-dipole interaction between the weakly solvating solvent B and the strongly polar solvent A includes electron-deficient H... δ+ With rich electrons O δ⁻ Interactions and / or 1 H- 1 H-dipole interaction; Preferably, the lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalate)borate, lithium difluorooxalateborate, or lithium hexafluoroarsenate.
[0015] Preferably, the inorganic filler is selected from lithium lanthanum zirconium oxide (Li7La3Zr2O) 12 LLZO), lithium lanthanum zirconium tantalum oxide (Li 6.4 La3Zr 1.4 Ta 0.6 O 12 LLZTO), surface-coated Li x TaO x F 5-x Lithium lanthanum zirconium tantalum oxide (LLZTO@LTOF), lithium titanium aluminum phosphate (Li 1.4 Al 0.4 Ti 1.6 (PO4)3, LATP), lithium aluminum germanium phosphate (Li 1.5 Al 0.5 Ge 1.5 (PO4)3, LAGP) or lithium lanthanum titanium oxide (Li 0.5 La 0.5 One or more of TiO3, LLTO, preferably surface-coated Lix TaO x F 5-x Lithium lanthanum zirconium tantalum oxide (LLZTO@LTOF).
[0016] The inorganic filler is first surface-coated before being added to the system; the surface coating layer is Li. x TaO x F 5-x ,in, x The surface coating treatment involves uniformly mixing TaF5, Li2CO3, and inorganic fillers through mechanical ball milling, followed by heat treatment at a specific temperature. The amount of TaF5 relative to the inorganic filler is 2-12 wt%, and the amount of Li2CO3 relative to the inorganic filler is 2-8 wt%. The treatment temperature is 150-300 °C, and the treatment time is 6-12 h. The mechanical ball milling speed is 200-300 rpm, and the milling time is 3-6 h.
[0017] Preferably, the total content of residual solvent (strong polar solvent A and weak solvating solvent B) in the composite solid electrolyte is ≤10 wt%, more preferably ≤6 wt%.
[0018] This invention also provides a method for preparing a composite solid electrolyte, comprising the following steps: (1) Mix the strong polar solvent A and the weak solvating solvent B in a preset ratio to form a mixed solvent; (2) Dissolve the lithium salt in the mixed solvent and stir until homogeneous to obtain a lithium salt solution; (3) Add the polymer matrix to the lithium salt solution, heat it to a certain temperature, and stir for a certain time to completely dissolve the polymer; (4) Add inorganic filler to the solution obtained in step (3), stir evenly, and obtain precursor slurry; (5) The precursor is cast into a film and dried to obtain the composite solid electrolyte; The molar ratio of the weak solvating solvent B to the strong polar solvent A is 1:4 to 4:1, preferably 1:2 to 2:1.
[0019] The concentration of the lithium salt is 0.5~5 M, and the stirring time is 2~6 hours.
[0020] In step (3), the heating temperature is 35~60℃ and the stirring time is 4~10 hours.
[0021] The mass ratio of the inorganic filler to the polymer matrix in step (4) is 1:10 to 1:1.
[0022] The drying temperature in step (5) is 60-100℃, the drying time is 6-48 hours, and the drying atmosphere is one of air, argon, and nitrogen.
[0023] The preparation method further includes a step of surface coating the inorganic filler, wherein the surface coating layer is Li. x TaO x F 5-x .
[0024] The present invention provides a solid lithium metal battery, comprising a positive electrode, a negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode, wherein the electrolyte layer is a composite solid electrolyte prepared by the above method.
[0025] Preferably, the positive electrode comprises lithium iron phosphate (LFP) or nickel-cobalt-manganese ternary material (NCM811).
[0026] Preferably, the negative electrode is lithium metal.
[0027] The application of the composite solid electrolyte or the solid lithium metal battery in energy storage devices, electric vehicles, and portable electronic devices should all be included within the scope of protection of this invention.
[0028] Compared with the prior art, the present invention has the following beneficial effects: (1) Proposing a novel control dimension: This invention is the first to propose using the dipole-dipole interaction between solvents as a new dimension for controlling CSE performance, breaking away from the traditional research that only focuses on solvent-Li + A single cognitive framework for understanding solvent-polymer and solvent-filler interactions. This is achieved by introducing the H+ interaction between weakly solvated solvents and residual strongly polar solvents. δ⁺ -O δ⁻ Dipole-dipole interactions systematically weaken multiple strong interactions associated with strongly polar solvents from the source, enabling synergistic regulation of solvent chemistry and interfacial chemistry, and fundamentally solving the dilemma between ionic conductivity and interfacial stability.
[0029] (2) Simultaneous enhancement of bulk ion transport and interfacial stability: This invention achieves multiple synergistic effects by inducing a redistribution of electron cloud density in strongly polar solvents through dipole-dipole interactions: (i) promoting the formation of anion-dominated solvation structures and reducing the desolvation energy barrier; (ii) weakening the strong dipole-dipole interaction between the solvent and polymer chains, thus removing transport restrictions along the polymer chains; (iii) enhancing the Li-linkage between the solvation structures and inorganic fillers. + Switching rate, eliminating interface Li + Flux unevenness. The resulting CSE exhibited an ionic conductivity of 1.70 mS / cm. -1 Li +The migration number reached 0.81, and the residual solvent content was only 4.3%, which is significantly better than the level reported in the prior art.
[0030] (3) Constructing a stable interface rich in inorganic components: This invention induces TFSI through anion-rich solvation structure. - Preferential decomposition at the electrode interface forms a fast-ion conductor SEI / CEI layer rich in LiF / Li2S / Li3N, effectively suppressing interfacial side reactions and lithium dendrite growth. The Li||CSE-DCP||Li symmetric cell operates at 1 mA cm⁻¹. -2 It can cycle stably for over 2600 hours at low temperatures and still cycle for over 800 hours at -20°C, demonstrating excellent interface stability.
[0031] (4) Achieving ultra-long cycle life and high energy density: The electrolyte-matched NCM811 cathode of this invention retains 92.7% capacity after 4000 cycles at 5C and maintains a high capacity retention of 83.4% after 5500 cycles at 10C. This is far superior to the 60% capacity retention after 2000 cycles in existing technologies. A high-load soft-pack battery achieves 306 Wh / kg capacity. -1 The energy retention rate of 86.3% after 400 cycles confirms the practical application potential of this invention.
[0032] (5) The preparation process is simple, the cost is controllable and the applicability is universal: the preparation method of the present invention is compatible with the existing CSE preparation process, without the need for special equipment or complex procedures, and the strategy is applicable to a variety of weak solvation solvents (ether solvents, fluorinated pyridine and fluorinated amide, etc.), and has good prospects for large-scale application.
[0033] This invention reveals and utilizes the orthogonal control dimension of inter-solvent dipole-dipole interaction, providing a novel strategic basis for overcoming the challenge of synergistic optimization of ion conduction and interface stability in composite solid electrolytes, which is of great significance for promoting the practical application of high-energy-density solid lithium metal batteries. Attached Figure Description
[0034] Figure 1 In the diagram, (a) represents different lithium salt solutions. 7 Li NMR spectra, (b) show different lithium salt solutions. 19 F nuclear magnetic resonance spectrum; Figure 2 In the image, (a) shows the Raman spectrum of the C=O bond in the lithium salt solution, and (b) shows the Raman spectrum of the COC bond in the lithium salt solution. Figure 3 In the image, (a) is the Fourier transform infrared spectrum of the C=O bond in the lithium salt solution, and (b) is the Fourier transform infrared spectrum of the COC bond in the lithium salt solution. Figure 4In the diagram, (a) represents different solvents. 17 O nuclear magnetic resonance spectra, (b) for different solvents 1 H nuclear magnetic resonance spectrum; Figure 5 In the image, (a) shows the Fourier transform infrared spectra of C=O bonds in different solvents, and (b) shows the Fourier transform infrared spectra of COC bonds in different solvents. Figure 6 In the diagram, (a) represents a mixed solvent. 1 H- 1 The two-dimensional correlation spectrum of H, (b) is the lithium salt solution prepared with mixed solvent. 1 H- 1 Two-dimensional correlation spectrum of H; Figure 7 In the table, (a) shows the calculated radial distribution function and coordination number of the composite electrolyte CSE-DM prepared with pure DMF solvent, and (b) shows the calculated radial distribution function and coordination number of the composite electrolyte CSE-DCP prepared with mixed solvent. Figure 8 The results are Raman analysis results for two electrolytes, CSE-DM and CSE-DCP. Figure 9 In the figure, (a) shows the two-dimensional structure of the CSE-DM electrolyte. 1 H- 19 F is the solid-state NMR spectrum of heteronuclear chemical shift correlation, and (b) is the two-dimensional NMR spectrum of CSE-DCP electrolyte. 1 H- 19 F heteronuclear chemical shift-related solid-state NMR spectroscopy; Figure 10 Thermogravimetric analysis and differential thermogravimetric analysis curves for two solid electrolytes, CSE-DM and CSE-DCP; Figure 11 Linear sweep voltammetry curves for two solid electrolytes, CSE-DM and CSE-DCP; Figure 12 Electrochemical impedance spectroscopy for two solid electrolytes, CSE-DM prepared in Comparative Example 1 and CSE-DCP prepared in Example 1; Figure 13 In the table, (a) shows the ion transport number test results of the CSE-DCP composite solid electrolyte prepared in Example 1, and (b) shows the ion transport number test results of the CSE-DM composite solid electrolyte prepared in Comparative Example 1. Figure 14 The activation energy fitting curves for the two solid electrolytes, CSE-DM prepared in Comparative Example 1 and CSE-DCP prepared in Example 1; Figure 15 Lithium-symmetric batteries assembled with two solid electrolytes prepared for Comparative Example 1 and Example 1 were tested at 25°C and 1 mA cm⁻¹.-2 Cyclic performance test graph at current density; Figure 16 The graph shows the long-cycle performance test results of the two solid electrolytes, NCM ternary cathode material and lithium metal assembled by Comparative Example 1 and Example 1 at 25°C and 5C rate. Figure 17 The graph shows the long-cycle performance test results of the full cells assembled with the two solid electrolytes prepared in Comparative Example 1 and Example 1 at 40°C and 10 C rate. Figure 18 The graph shows the long-cycle performance test results of the full cells assembled with the two solid electrolytes prepared in Comparative Example 1 and Example 1 at -20°C and 0.5 C rate. Figure 19 The graph shows the cycle performance of the CSE-DCP composite solid electrolyte prepared in Example 1 after it was assembled into a pouch cell at 25°C and 0.5 C rate. Detailed Implementation
[0035] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. These embodiments are based on the technical solution of the present invention and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.
[0036] Unless otherwise specified in the examples, the procedures were performed under standard conditions or as recommended by the manufacturer. Reagents or instruments whose manufacturers were not specified were all commercially available products.
[0037] This invention is the first to discover and utilize the intermolecular dipole-dipole interaction between a weakly solvating solvent and a strongly polar solvent. This interaction can induce a redistribution of the electron cloud density in the strongly polar solvent, systematically weakening its interaction with Li. + The strong interactions between polymers and fillers enable the simultaneous achievement of high ionic conductivity and high Li content. + The discovery reveals excellent transference numbers and interfacial stability. This finding breaks through the limitations of existing technologies that rely on "single solvent-ion interactions," providing a new design dimension for optimizing the performance of composite solid electrolytes.
[0038] This invention provides a composite solid electrolyte based on inter-solvent dipole-dipole interactions and its preparation method, specifically including the following steps: Step (1) Solvent mixing: The weakly solvating solvent B and the strongly polar solvent A are mixed in a molar ratio of 1:4 to 4:1, preferably 1:2 to 2:1. After stirring for 1 to 4 hours, the solvents are uniformly mixed to obtain a mixed solvent. Preferably, in this step, the weakly solvating solvent B is one or more of cyclopentyl methyl ether, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, methyl tert-butyl ether, ethyl tert-butyl ether, fluoropyridine, tributyl phosphate, sulfolane, N,N-dimethyltrifluoromethanesulfonamide, trifluoroacetamide, N-methoxy-N-methyltrifluoromethanesulfonamide, N-methyltrifluoroacetamide, N,N-dimethyltrifluoroacetamide, or fluorophenylphosphine; the strongly polar solvent A is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, dimethyl sulfoxide, or carbonate solvents.
[0039] Step (2) Dissolving the lithium salt: Add a certain amount of lithium salt to the mixed solvent obtained in step (1) and stir for 2-6 hours until completely dissolved to obtain a lithium salt solution. Preferably, the lithium salt in this step is one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalate)borate, lithium difluorooxalateborate, or lithium hexafluoroarsenate; the concentration of the lithium salt in the mixed solvent is 0.5-5 M.
[0040] Step (3) Slurry preparation: Add polymer matrix to the above lithium salt solution, heat to 35~60℃ and stir continuously for 4~10 hours to completely dissolve the polymer matrix and obtain polymer solution. Then add inorganic filler to the obtained polymer solution and stir for 2~6 hours to form a uniform precursor slurry.
[0041] The polymer matrix mentioned in this step is selected from one or more of polyethylene, polypropylene, polyvinyl chloride, polyvinylidene fluoride, polyvinylidene fluoride cohexafluoropropylene, polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, or polyvinylidene chloride; the inorganic filler is selected from lithium lanthanum zirconium oxide (Li7La3Zr2O) 12 LLZO), lithium lanthanum zirconium tantalum oxide (Li 6.4 La3Zr 1.4 Ta 0.6 O 12 LLZTO), surface-coated Li x TaO x F 5-x Lithium lanthanum zirconium tantalum oxide (LLZTO@LTOF), lithium titanium aluminum phosphate (Li 1.4 Al 0.4 Ti 1.6 (PO4)3, LATP), lithium aluminum germanium phosphate (Li 1.5 Al 0.5 Ge 1.5(PO4)3, LAGP) or lithium lanthanum titanium oxide (Li 0.5 La 0.5 One or more of TiO3, LLTO; the mass ratio of the inorganic filler to the polymer matrix is 1:10 to 1:1; The inorganic filler is first surface-coated before being added to the system; the surface coating layer is Li. x TaO x F 5-x ,in, x The surface coating treatment involves uniformly mixing TaF5, Li2CO3, and inorganic fillers through mechanical ball milling, followed by heat treatment at a specific temperature. The amount of TaF5 relative to the inorganic filler is 2-12 wt%, and the amount of Li2CO3 relative to the inorganic filler is 2-8 wt%. The treatment temperature is 150-300 °C, and the treatment time is 6-12 h. The mechanical ball milling speed is 200-300 rpm, and the milling time is 3-6 h.
[0042] Step (4) Film formation: The precursor slurry is cast into a polytetrafluoroethylene mold and dried to obtain the composite solid electrolyte membrane. The drying temperature in this step is 60-100℃, the drying time is 6-48 hours, and the drying atmosphere is one of air, argon, and nitrogen.
[0043] In the prepared composite solid electrolyte, the dipole-dipole interaction between the weakly solvating solvent B and the strongly polar solvent A induces a redistribution of the electron cloud density of the strongly polar solvent, weakening its interaction with Li. + The interaction between the polymer matrix and the inorganic filler promotes rapid Li-linkage between the interfacial solvated structure and the inorganic filler. + Exchange enhances Li transport kinetics. Furthermore, it reduces the content of unstable residual highly polar solvents, induces the formation of anion-rich solvated structures, and significantly improves interfacial stability.
[0044] The mechanism of this invention will be explained using N,N-dimethylformamide (DMF) as a strongly polar solvent A and cyclopentylmethyl ether (CPME) as a weak solvating solvent B as an example.
[0045] Because DMF has a higher highest occupied molecular orbital (HOMO) and a lower lowest occupied molecular orbital (LUMO) compared to CPME, it is prone to decomposition at the electrolyte / electrode interface. CPME, on the other hand, is stable to lithium metal, reducing the occurrence of interfacial side reactions.
[0046] To demonstrate that the introduction of CPME can weaken the solvation ability of the solvent, this invention prepared solutions with a concentration of 10 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) using a mixed solvent, pure DMF, and CPME (named Li-DMF / CPME, Li-DMF, and Li-CPME, respectively). 7 Li and 19 Liquid nuclear magnetic resonance (NMR) measurements were used to elucidate the solvation structure dynamics. In the Li-DMF / CPME, the molar ratio of DMF to CPME was 1:1.
[0047] Figure 1 (a) shows different lithium salt solutions 7 Li NMR spectrum, Figure 1 (b) For different lithium salt solutions 19 F NMR spectrum. Li-DMF / CPME relative to Li-DMF. 7 Li and 19 The F peaks all shifted upwards, indicating a weakening of Li. + - Solvent coordination and enhanced Li +- TFSI - Function. The electrostatic potentials of DMF and CPME and their effect on Li were calculated theoretically. + The binding energy revealed that COC (-1.47 eV) in CPME has a weaker electronegativity than C=O (-2.2 eV) in DMF, leading to Li + -The binding energy of CPME (-90.28 kJ mol) -1 Compared to Li + -DMF (-96.14 kJ mol) -1 The low concentration of cyclopentyl groups, coupled with the large cyclopentyl groups, hinders the interaction with Li. + Coordination, leading to its interaction with Li + The coordination ability is relatively weak. The above results indicate that partially replacing DMF with CPME can weaken the Li... + - Solvent action promotes anionic TFSI - It participates in solvation.
[0048] Figure 2 The Raman spectra shown are Figure 3 The Fourier transform infrared spectrum shown confirms the coordination in the solvated structure. Figure 2 Raman spectra of C=O and COC bonds in lithium salt solutions. Figure 3 Infrared spectra of C=O and COC bonds in lithium salt solutions. The blue shift of the C=O resonance peak in Li-DMF and the COC resonance peak in Li-CPME indicates a decrease in the electron cloud density around the O atom, which is attributed to the interaction with Li. +Coordination-induced. The C=O and COC resonance peaks in Li-DMF / CPME are blue-shifted and red-shifted relative to Li-DMF and Li-CPME, respectively, indicating an interaction between DMF and CPME.
[0049] This invention provides a detailed analysis of the solvent system through systematic spectroscopic characterization and theoretical calculations to investigate the existence and impact of the interaction between the two solvents. Figure 4 (a) for different solvents 17 O NMR spectrum, Figure 4 (b) for different solvents 1 1H NMR spectrum. DMF / CPME mixed solvent 17 The O NMR spectra of relatively pure DMF and CPME show significant downward and upward field shifts, respectively, while 1 The H NMR spectra show significant up-field and down-field shifts, respectively, indicating a strong electron-deficient H NMR relationship between DMF and CPME. δ+ With Rich Electronics O δ- Dipole-dipole interactions. Furthermore, such as... Figure 5 As shown, the blue shift of the infrared resonance peak of C=O and the red shift of the resonance peak of COC in the mixed solvent further prove that the addition of CPME induces intermolecular dipole-dipole interactions that weaken the electron cloud density of C=O while increasing the electron cloud density of COC, resulting in an increase in the strength of C=O bonds and a decrease in the strength of COC bonds.
[0050] In addition, two-dimensional correlation spectroscopy (2D-COSY) also revealed the properties of the mixed solvents. 1 H- 1 H-coupling. For example, Figure 6 As shown, Figure 6 (a) is a mixed solvent 1 H- 1 2D-COSY of H, besides the solvent molecule 1 H- 1 H-coupled signals also showed intermolecular coupling at the off-diagonal points. 1 H- 1 H coupling. This is attributed to H. δ+ -O δ- Driven by the interaction, the distance between DMF and CPME solvent molecules decreases, leading to overlap of H electron clouds. Due to the closer distance, intramolecular... 1 H-coupled signal strength is typically higher than that between molecules. Figure 6 (b) for in Figure 6 (a) is based on the dissolution of lithium salt to form a solution. 1 H- 1 The solubility of H in 2D-COSY and LiTFSI further enhances the solvent interaction.1 H- 1 H-coupling effect, which is attributed to Li + The ionic dipole interaction between CPME and the solvent induces the electron cloud to polarize towards the O atom, thereby enhancing the electronegativity of O and the electronegativity of H in a single solvent molecule, further shortening the distance between solvent molecules. These results demonstrate a strong H-relationship between CPME and DMF. δ+ - O δ- and 1 H- 1 H-dipole-dipole interactions effectively adjust the electron cloud density and distribution between solvent molecules.
[0051] Using PVDF-HFP as the polymer matrix, LiTFSI as the lithium salt (PVDF-HFP to LiTFSI mass ratio of 2:1), and LLZTO@LTOF as the inorganic filler (the amount of inorganic filler is 30 wt% of the total amount of PVDF-HFP and LiTFSI), CSEs (labeled CSE-DM and CSE-DCP, respectively, with a DMF to CPME molar ratio of 1:1) were prepared using pure DMF and a mixed solvent DMF / CPME. To clearly elucidate the effect of dipole-dipole interactions in the mixed solvent on the electrolyte solvation structure, the radial distribution function (RDF) and coordination number (CN) of CSE-DM and CSE-DCP were calculated using molecular dynamics simulations. Figure 7 As shown, Li in CSE-DCP + With CPME O (CPME) A coordination number of 0.308 indicates that CPME participates in the internal solvation of the sheath. Compared to CSE-DM, the introduction of CPME leads to Li + With O in DMF solvent (DMF) The coordination number decreased from 1.692 to 0.321, compared to O (TFSI-) The coordination number increased from 1.974 to 2.762, indicating the formation of more aggregated ion pairs (AGGs). Figure 8 The Raman spectroscopy results for CSE-DM and CSE-DCP electrolytes also demonstrate the formation of more anion-involved solvation structures in the CSE-DCP electrolyte. The lithium salt anions in these solvation structures preferentially decompose during cycling, forming anion-rich conductor positive solid electrolyte interlayer (CEI) and a negative solid electrolyte interlayer (SEI), enhancing interfacial stability and Li... + Transport dynamics.
[0052] This invention also utilizes two-dimensional... 1 H- 19 F heteronuclear chemical shift correlation (2D) 1 H- 19F) Solid-state NMR analysis was used to investigate the effect of dipole-dipole interactions on atypical hydrogen bonding between the solvent and PVDF-HFP. The results are as follows: Figure 9 As shown, where Figure 9 (a) is a 2D representation of CSE-DM 1 H- 19 F NMR spectrum, Figure 9 (b) is the 2D of CSE-DCP 1 H- 19 F NMR spectrum. In CSE-DM electrolyte, DMF in... 1 H(-CH3) and PVDF-HFP 19 The presence of a strong correlation peak at F indicates a strong dipole-dipole interaction between DMF and PVDF-HFP. However, a small CPME-PVDF-HFP correlation peak was observed in the CSE-DCP electrolyte, indicating a weak interaction between CPME and the polymer. Furthermore, the DMF-PVDF-HFP correlation peak became smaller and flatter, demonstrating that the dipole-dipole interaction weakens the interaction between DMF / PVDF-HFP and facilitates faster diffusion of solvated structures. Density functional theory calculations were used to assess the effect of the dipole-dipole interaction on the interaction strength between the solvent and the polymer, and the filler. The adsorption energies between DMF-PVDF-HFP (-0.285 eV) and DMF-LTOF (-1.81 eV) are greater than those between CPME-PVDF-HFP (-0.119 eV) and CPME-LTOF (-1.07 eV), respectively, indicating a strong interaction. This strong interaction not only severely hinders the migration of solvated structures along the polymer chain but also causes the electrolyte to retain a large amount of unstable solvent, reducing interfacial stability. When CPME partially replaces DMF to introduce dipole-dipole interactions, the adsorption energies of DMF-PVDF-HFP and DMF-LTOF decrease to -0.186 eV and -1.34 eV, respectively, effectively weakening the interaction between DMF and the polymer and filler, and breaking the Li + The restriction of transport along the polymer chain increases ionic conductivity.
[0053] Thermogravimetric analysis was performed on CSE-DM and CSE-DCP, such as Figure 10 As shown, the CSE-DM electrolyte contained 8.1 wt% residual solvent, while the CSE-DCP electrolyte showed a significantly lower residual solvent content of only 4.3 wt%, effectively reducing side reactions caused by solvent decomposition. The electrochemical windows of the two electrolytes were also tested, and the results are shown below. Figure 11As shown, the electrochemical window of CSE-DM is 4.96 V. Due to the lower residual solvent content and low desolvation energy barrier in CSE-DCP electrolyte, the interfacial solvent decomposition is effectively suppressed, thereby widening the electrochemical window to 5.14 V, showing good matching potential with high-voltage cathode.
[0054] The above results indicate that the mixed solvent formed by partially replacing the strongly polar solvent DMF with weakly solvated CPME not only exhibits solvent-dependent Li... + The competitive coordination between the solvent and the solvent is more important than the dipole-dipole interaction, which promotes the redistribution of the electron cloud density of the DMF and weakens the interaction between the solvent and Li. + The multiple strong interactions between the polymer and inorganic fillers relieved the solvent-dominated solvation structure from the influence of the interface Li. + Exchange binding induces the formation of anion-rich solvated structures, thereby reducing Li + Desolvation energy barrier. This mechanism plays a key role in promoting the formation of stable SEI and CEI, improving ionic conductivity, and enhancing the stability of the electrolyte / electrode interface.
[0055] To facilitate understanding of the embodiments of the present invention, the present invention will be further described below with reference to the accompanying drawings and examples, but is not limited thereto.
[0056] Example 1 First, LLZTO powder and TaF5 were mixed at a mass ratio of 100:9, and then treated at 200°C for 8 hours under an Ar atmosphere to obtain Li. x TaO x F 5-x Encapsulated LLZTO (labeled LLZTO@LTOF).
[0057] A mixed solvent was prepared by mixing DMF and CPME at a molar ratio of 1:1 and stirring for 1 hour. A lithium salt solution was prepared by dissolving 10 M LiTFSI in the mixed solvent and stirring for 2 hours until completely dissolved. PVDF-HFP (mass ratio of PVDF-HFP to LiTFSI of 2:1) was added to the resulting lithium salt solution and stirred at 60°C for 3 hours until completely dissolved. Then, LLZTO@LTOF filler (mass ratio of filler to polymer PVDF-HFP of 1:2) was added, and stirring continued for 6 hours to obtain a homogeneous precursor slurry. The slurry was cast onto a polytetrafluoroethylene plate and dried under nitrogen at 60°C for 24 hours to obtain the CSE-DCP composite solid electrolyte.
[0058] NCM811 active material, PVDF (binder), and Super P (conductive carbon black) were weighed in a mass ratio of 8:1:1, and 0.32 g, 0.04 g, and 0.04 g of each were weighed into a mortar. The mixture was first dry-ground for 10 minutes, then 1.5 mL of N-methylpyrrolidone (NMP) was added, and the mixture was ground for another 15 minutes to obtain the positive electrode slurry. Finally, the positive electrode slurry was coated onto an Al foil and dried in a vacuum oven at 90°C for 12 hours to obtain the positive electrode sheet.
[0059] A lithium-symmetric battery was assembled by combining the CSE-DCP composite solid electrolyte with two lithium metal plates; a full battery was assembled by combining the positive electrode plate, the CSE-DCP composite solid electrolyte, and lithium metal plates.
[0060] Comparative Example 1 The only difference from Example 1 is that CPME is not added, and only DMF is used as a single solvent. The remaining steps are the same as in Example 1 to obtain CSE-DM composite solid electrolyte, and lithium symmetric cells and full cells are assembled in the same way.
[0061] Electrochemical performance comparison between Example 1 and Comparative Example 1 The ionic conductivity of the composite solid electrolytes prepared in Example 1 and Comparative Example 1 was measured using electrochemical impedance spectroscopy. Figure 12 As shown, the ionic conductivity of CSE-DCP prepared in Example 1 is 1.70 × 10⁻⁶. -3 S cm -1 The ionic conductivity of the CSE-DM prepared in Comparative Example 1 was 1.12 × 10⁻⁶. -3 S cm -1 .
[0062] Li was tested simultaneously with two electrolytes. + Number of migrations, results as follows Figure 13 As shown, where Figure 13 (a) shows the CSE-DCP ion transport number test results for Example 1. Figure 13 (b) shows the ion transport number test results of CSE-DM in Comparative Example 1. The ion transport number of CSE-DCP is 0.81, which is significantly higher than that of CSE-DM (0.59).
[0063] In addition, the activation energies of the two composite solid electrolytes were tested using variable-temperature electrochemical impedance spectroscopy, and the results are as follows: Figure 14 As shown, the activation energy of CSE-DM is 0.259 eV, while that of CSE-DCP decreases to 0.177 eV. These results indicate that the dipole-dipole interaction between DMF and CPME can break the Li... + Transport restriction promotes Li in the electrolyte + Conduction.
[0064] Long-term lithium plating / stripping cycle tests were conducted on the lithium symmetric batteries Li|CSE-DCP|Li and Li|CSE-DM|Li assembled with the two composite solid electrolytes prepared in Example 1 and Comparative Example 1. Figure 15 These are two types of lithium symmetric batteries at 25°C, l mAcm -2 The cycling diagram at current density shows that Li|CSE-DCP|Li can be stably plated / stripped for more than 2600 hours, while Li|CSE-DM|Li can only be plated / stripped for about 500 hours, and the polarization voltage increases rapidly, leading to rapid failure of the symmetrical cell.
[0065] In addition, the full cells assembled in Example 1 and Comparative Example 1 were subjected to long-cycle tests. Figure 16 These are the long-cycle performance test graphs of two full cells at 25°C and 5 C rate. The full cell assembled by CSE-DCP prepared in Example 1 can stably cycle 4000 times at 5 C with a capacity retention of up to 92.7% and a coulombic efficiency close to 100%, while the full cell assembled by CSE-DM prepared in Comparative Example 1 has a capacity retention of only 45.5%. Figure 17 These are the long-cycle performance test graphs of two full cells at 40°C and 10 C rate. The full cell assembled by CSE-DCP prepared in Example 1 was stably cycled for 5500 cycles at 10 C with a capacity retention of up to 83.4%, while the full cell assembled by CSE-DM prepared in Comparative Example 1 experienced rapid capacity decay due to severe interfacial side reactions, with a capacity retention of only 19.2%. The cycling stability of the two full cells at low temperatures was also compared. Figure 18 These are the long-cycle performance test graphs of two full cells at -20°C and 0.5C rate. The full cell assembled from CSE-DCP prepared in Example 1 has an initial specific capacity of 157.3 mAh g⁻¹. -1 The first cell was able to cycle stably for over 500 cycles with a capacity retention of 83.9%; while the initial specific capacity of the CSE-DM assembled cell prepared in Comparative Example 1 was only 33.1 mAh g⁻¹. -1 The capacity decays rapidly and the coulombic efficiency is low, leading to a rapid short circuit in the battery due to severe interfacial reactions.
[0066] A pouch cell was assembled using the CSE-DCP electrolyte from Example 1, with NCM811 (area capacity 3.78 mAh / cm³) as the positive electrode. -2 The negative electrode is a 50 μm lithium foil with an N / P ratio of 3.1. Figure 19 This is a cycling performance graph of a pouch cell assembled with the composite solid electrolyte prepared in Example 1 at 25°C and a 0.5 C rate. The results show that the pouch cell has a capacity of 37.8 mAh and an energy density of 306 Wh kg at 0.1 C. -1After 400 cycles at 0.5C, the capacity retention rate was 86.3%, demonstrating excellent potential for practical applications.
[0067] The results of the above measurements of the electrochemical performance of the composite solid electrolyte, symmetrical cell, and full cell demonstrate that the method described in this invention can effectively improve the electrolyte's ion conductivity and electrolyte / electrode interface stability by introducing dipole-dipole interactions into the composite electrolyte.
[0068] Example 2 The difference from Example 1 is that DMF was replaced with dimethylacetamide (DMAc) and CPME was replaced with ethylene glycol dimethyl ether (DME), while the remaining steps were the same as in Example 1. Ionic conductivity, ion transport number, and activation energy were tested on the above composite solid electrolyte, and the results showed that the ionic conductivity of the prepared composite solid electrolyte was 1.92 × 10⁻⁶. -3 S cm -1 The ion transference number is 0.84 and the activation energy is 0.157 eV.
[0069] Comparative Example 2 To demonstrate the crucial role of solvent-to-solvent interactions in this invention, this comparative example uses the same DMF and CPME molar ratio as Example 1. However, by pre-mixing DMF and CPME separately with the lithium salt before combining them, sufficient contact between DMF and CPME during the mixing process is avoided, thereby suppressing the formation of solvent-to-solvent dipole-dipole interactions. Specific steps: First, 1M LiTFSI is dissolved in DMF, then 1M LiTFSI is dissolved in CPME. The two solutions are then mixed, and subsequent steps are the same as in Example 1. A non-interacting composite solid electrolyte is obtained.
[0070] The ionic conductivity, ion transport number, and activation energy of the above-mentioned composite solid electrolyte were tested, and the results showed that the ionic conductivity of the prepared composite solid electrolyte was 1.04 × 10⁻⁶. -3 S cm -1 The ion transference number is 0.60 and the activation energy is 0.247 eV. Compared with Example 1 (mixing the solvent first and then dissolving the lithium salt), the preparation sequence in this comparative example results in insufficient contact between DMF and CPME before dissolving the lithium salt, which affects the degree of formation of the dipole-dipole interaction between the solvents.
[0071] This demonstrates that solvent-to-solvent interactions are key to performance enhancement. Electrochemical performance tests were also conducted on lithium symmetric and full cells assembled with this electrolyte. The assembled symmetric cell achieved a performance of 1 mA cm⁻¹. -2Under stable current density, electroplating / stripping only lasted 800 hours before a short circuit occurred, which was far worse than Example 1. Although there was an improvement compared to Comparative Example 1 (approximately 500 hours), it still did not meet the requirements for practical applications. After 2000 cycles at the same temperature as Example 1, the capacity retention rate of Comparative Example 2 dropped to 50%, and the degradation accelerated in the later stages.
[0072] The above results indicate that fully establishing inter-solvent dipole-dipole interactions during the mixed solvent stage is key to achieving performance improvement.
[0073] Example 3 The difference from Example 1 is that DMF is replaced with NMP and CPME is replaced with fluoropyridine; the remaining steps are the same as in Example 1. Ionic conductivity, ion transport number, and activation energy of the above composite solid electrolyte were tested, and the results showed that the ionic conductivity of the prepared composite solid electrolyte was 1.74 × 10⁻⁶. -3 S cm -1 The ion transference number is 0.87 and the activation energy is 0.168 eV.
[0074] Comparative Example 3 The difference from Example 3 is that fluoropyridine was not added; NMP was used as the sole solvent. The remaining steps were the same as in Example 3, yielding a composite solid electrolyte. Ionic conductivity, ion transport number, and activation energy were tested on the above composite solid electrolyte, revealing that the prepared composite solid electrolyte has an ionic conductivity of 1.0 × 10⁻⁶. -3 S cm -1 The ion transference number is 0.49 and the activation energy is 0.298 eV.
[0075] Example 4 A mixed solvent was prepared by mixing dimethyl sulfoxide and N-methoxy-N-methyltrifluoroethanesulfonamide at a molar ratio of 1:1 and stirring for 2 hours. A lithium salt solution was prepared by dissolving 2 M LiTFSI in the mixed solvent and stirring for 3 hours until completely dissolved. Polyethylene oxide (PEO) (at a mass ratio of 1:1 to LiTFSI) was added to the resulting lithium salt solution and stirred at 60°C for 4 hours until completely dissolved. Then, LATP filler (at a mass ratio of filler to PEO polymer of 1:3) was added, and stirring continued for 8 hours to obtain a homogeneous precursor slurry. The slurry was cast onto a polytetrafluoroethylene plate and dried under nitrogen at 60°C for 16 hours to obtain a composite solid electrolyte.
[0076] The ionic conductivity, ion transport number, and activation energy of the above-mentioned composite solid electrolyte were tested, and the results showed that the ionic conductivity of the prepared composite solid electrolyte was 1.74 × 10⁻⁶. -3 S cm -1 The ion transference number is 0.88 and the activation energy is 0.161 eV.
[0077] The above examples and comparative examples fully demonstrate that the present invention differs from the strategy of simply replacing the solvent in the prior art. The key lies in utilizing the dipole-dipole interaction between the weakly solvating solvent and the strongly polar solvent. This interaction can fundamentally reconstruct the solvation structure, while simultaneously achieving a synergistic improvement in ionic conductivity and interfacial stability. The results of Comparative Example 2 further confirm that even when using the same weakly solvating solvent, without the interaction between solvents, the performance improvement is limited and cannot achieve the technical effect of the present invention.
[0078] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A composite solid electrolyte based on inter-solvent dipole-dipole interactions, characterized in that, The electrolyte comprises: a polymer matrix, a lithium salt, an inorganic filler, and a solvent system, wherein the solvent system comprises a strongly polar solvent A and a weakly solvating solvent B; wherein... The highly polar solvent A and Li + The polymer matrix and inorganic filler have strong coordination or dipole-dipole interactions; The weakly solvating solvent B for Li + The coordination ability, polymer matrix, and inorganic filler coordination strength are weaker than those of the strongly polar solvent A; An intermolecular dipole-dipole interaction exists between the weakly solvating solvent B and the strongly polar solvent A. This dipole-dipole interaction induces a redistribution of the electron cloud density in the strongly polar solvent A, thereby weakening the interaction between the strongly polar solvent A and Li. + The strength of the interaction between the polymer matrix and the inorganic filler.
2. The composite solid electrolyte according to claim 1, characterized in that, The strongly polar solvent A is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, dimethyl sulfoxide, or carbonate solvents; The weak solvating solvent B is selected from one or more of the following: ether solvents, fluorinated amide solvents, fluorinated pyridine solvents, phosphate ester solvents, or fluorinated sulfonamide solvents.
3. The composite solid electrolyte according to claim 1 or 2, characterized in that, The molar ratio of the weak solvating solvent B to the strong polar solvent A is 1:4 to 4:
1.
4. The composite solid electrolyte according to claim 1, characterized in that, The dipole-dipole interaction between the weakly solvating solvent B and the strongly polar solvent A includes electron-deficient H atoms. δ+ With rich electrons O δ⁻ Interactions and / or 1 H- 1 H-dipole interaction; electron-deficient H on the weakly solvated solvent B δ+ With electron-rich O on the strongly polar solvent A δ⁻ Weak hydrogen bonds are formed between them, which serve as "bridging" sites between adjacent solvated structures, promoting the formation of conjugated solvation networks.
5. The composite solid electrolyte according to claim 1, characterized in that, The polymer matrix is selected from one or more of polyethylene, polypropylene, polyvinyl chloride, polyvinylidene fluoride, polyvinylidene fluoride cohexafluoropropylene, polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, or polyvinylidene chloride; The lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalate)borate, lithium difluorooxalateborate, or lithium hexafluoroarsenate. The inorganic filler is selected from lithium lanthanum zirconium oxide (Li7La3Zr2O). 12 LLZO), lithium lanthanum zirconium tantalum oxide (Li 6.4 La3Zr 1.4 Ta 0.6 O 12 LLZTO), surface-coated Li x TaO x F 5-x Lithium lanthanum zirconium tantalum oxide (LLZTO@LTOF), lithium titanium aluminum phosphate (Li 1.4 Al 0.4 Ti 1.6 (PO4)3, LATP), lithium aluminum germanium phosphate (Li 1.5 Al 0.5 Ge 1.5 (PO4)3, LAGP) or lithium lanthanum titanium oxide (Li 0.5 La 0.5 One or more of TiO3, LLTO.
6. The composite solid electrolyte according to claim 1, characterized in that, The total residual solvent content of the strongly polar solvent A and the weakly solvating solvent B in the composite solid electrolyte is ≤10 wt%.
7. A method for preparing a composite solid electrolyte as described in any one of claims 1-6, characterized in that, Includes the following steps: (1) Mix the strong polar solvent A and the weak solvating solvent B in a preset ratio to form a mixed solvent; (2) Dissolve the lithium salt in the mixed solvent and stir until homogeneous to obtain a lithium salt solution; (3) Add the polymer matrix to the lithium salt solution, heat and stir to completely dissolve the polymer; (4) Add inorganic filler to the solution obtained in step (3), stir evenly, and obtain precursor slurry; (5) The precursor is cast into a film and dried to obtain the composite solid electrolyte; The molar ratio of the weak solvating solvent B to the strong polar solvent A is 1:4 to 4:
1.
8. The preparation method according to claim 7, characterized in that, The concentration of the lithium salt solution in step (2) is 0.5~5M, and the stirring time is 2~6 hours; In step (3), the heating temperature is 35~60℃ and the stirring time is 4~10 hours; The mass ratio of the inorganic filler to the polymer matrix in step (4) is 1:10 to 1:1; The drying temperature in step (5) is 60-100°C, the drying time is 6-48 hours, and the drying atmosphere is one of air, argon, and nitrogen.
9. The preparation method according to claim 7, characterized in that, The inorganic filler is surface coated before step (4); the surface coating layer is Li x TaO x F 5-x The surface coating treatment is obtained by coating the inorganic filler surface with a precursor containing tantalum, oxygen and fluorine by liquid phase deposition and then heat treatment.
10. A solid-state lithium metal battery, comprising a positive electrode, a negative electrode, and an electrolyte layer between the positive and negative electrodes, characterized in that, The electrolyte layer comprises the composite solid electrolyte according to any one of claims 1-6.
Citation Information
Patent Citations
Composite solid electrolyte, preparation method thereof and lithium metal battery
CN116454370A
